2014
DOI: 10.1177/0954405414530694
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of constant pressure oil source fluctuations on ultra-precision machining

Abstract: The waviness errors on the machined surfaces have significant impact on the performance of optical components. Midspatial frequency errors (amplitude near 10 nm, wavelength about 1 mm) are found on the machined surfaces along feeding direction, and the oil pressure fluctuations of the hydrostatic slide are confirmed to be the main source which produces such waviness errors. In this article, the influence of oil pressure fluctuations on the machined surface is studied quantitatively for the first time, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This phenomenon is caused by the straightness error of the slide and fluctuation of the oil pressure in the machining process, which were neglected in the simulation model. 24 Furthermore, the damping radio for each mode is different in the real machine tool, but in the simulation model, the unified vale is adopted, which makes the amplitude of the waviness different between the test and the simulation results. On the whole, this simulation model is effective to predict the influence of multimode frequency vibration of the machine tool on the surface generation in the cutting direction.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is caused by the straightness error of the slide and fluctuation of the oil pressure in the machining process, which were neglected in the simulation model. 24 Furthermore, the damping radio for each mode is different in the real machine tool, but in the simulation model, the unified vale is adopted, which makes the amplitude of the waviness different between the test and the simulation results. On the whole, this simulation model is effective to predict the influence of multimode frequency vibration of the machine tool on the surface generation in the cutting direction.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al. 17 found some waviness errors on the finished surface of the KDP crystal. The amplitude of these waviness errors is about 10 nm, the wavelengths are gathered in the range of 0.5–1.…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that this kind of profile will reduce the laser-induced damage threshold (LIDT) of KDP optical elements. Chen et al 17 found some waviness errors on the finished surface of the KDP crystal. The amplitude of these waviness errors is about 10 nm, the wavelengths are gathered in the range of 0.5-1.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous research, some mid-frequency errors are found along the feeding direction. 19 The amplitude of these waviness errors is about 10 nm, and the wavelengths are gathered in the range of 0.5-1.5 mm. These errors are induced by the oil source pressure fluctuation of hydraulic system.…”
Section: Introductionmentioning
confidence: 99%